LONG-TERM IN THE FIELD OF INFORMATION AND COMMUNICATION TECHNOLOGIES FAIR VALUE OF ASSETS AND ITS REGULATORY LEGAL SUPPORT - Fayzullayev Behzod Baxtiyor ugli (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This article deals with the long-term in the field of information and communication technologies fair value of assets and its regulatory legal support explained. Also, the fair value of long-term assets and the problematic aspects arising in its determination are highlighted, and suggestions are made on them.